The Safety of Cardioversion in Supra Ventricular Tachycardia Patient with Pregnancy - Sugianto Mukmin; Erwin Sukandi; Abarham Martadiansyah (HM Publisher, 2021)
Backgrounds. Supraventricular tachycardia is a type of tachyarrhythmia characterized by sudden changes in heart rate and increases rapidly. In supraventricular tachycardia, the abnormalities that occur include components of the conduction system and occur in the upper part of the HIS bundle. This case report describes a case of supraventricular tachycardia suspected of AVNRT in a pregnant woman accompanied by hypokalemia, hypocalcemia and prolonged QT Interval along with cardioversion which was performed as the management of this case.Case presentation. A woman, Mrs Y, 24 years old, a housewife, having her address within the city of Palembang. The patient came to the emergency department of Moh. Hoesin Hospital Palembang with the chief complaint of chest palpitations. On physical examination, there was a grade 2/6 murmur, no shortness of breath, the patient was 7 months pregnant. He had a history of heart disease SVT 8 years ago. ECG examination showed sinus rhythm with low atrial rhythm in leads II, III, AVF. On laboratory examination, the blood calcium level was 8.3 mg/dL. Management of this patient includes pharmacological and non-pharmacological management. On the 14th day of hospitalization, 100 joules of cardioversion was performed and the patient responded well. The patient's condition improved on the 20th day of treatment.Conclusion. The patient experienced a good and effective response to 100 joules of cardioversion which was performed on the 14th day of treatment. Maintenance treatment in the form of drugs in the form of diltiazem due to the condition of the patient who is 27 weeks pregnant. The next management is planning the birth process according to the patient's hemodynamics and preventing the occurrence of SVT in subsequent pregnancies.